Two-dimensional simulations of pulsational pair-instability supernovae - Chen, Ke-Jung; Woosley, Stan; Heger, Alexander; Almgren, Ann; Whalen, Daniel J. (The astrophysical journal, 2014)
Massive stars that end their lives with helium cores in the range of 35-65 M ☉ are known to produce repeated thermonuclear outbursts due to a recurring pair-instability. In some of these events, solar masses of material are ejected in repeated outbursts of several × 1050 erg each. Collisions between these shells can sometimes produce very luminous transients that are visible from the edge of the observable universe. Previous one-dimensional (1D) studies of these events produce thin, high-density shells as one ejection plows into another. Here, in the first multi-dimensional simulations of these collisions, we show that the development of a Rayleigh-Taylor instability truncates the growth of the high-density spike and drives mixing between the shells. The progenitor is a 110 M ☉ solar-metallicity star that was shown in earlier work to produce a superluminous supernova. The light curve of this more realistic model has a peak luminosity and duration that are similar to those of 1D models but a structure that is smoother.